Kesehatan Mental dan Penanganan Gangguannya Secara Islami di Masa Kini - Syifa Diah Puspita (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2022)
Mental disorders if not handled properly, will get worse, and in the end can burden families, communities, and the government. The method used in this paper is to use descriptive exploratory analysis, through literature review and secondary data studies. The results of the study show that the study of the 2018 Riskesdas data revealed that the prevalence of severe mental disorders in the Indonesian population is 7% (per mile of the total population) and most were in Bali, Yogyakarta, NTB and Aceh. The mental emotional disorders with symptoms of depression and anxiety amounted to 9.8% and most were in Central Sulawesi, Gorontalo, NTT and Maluku. The mental health movement must prioritize prevention and the role of the community to help optimize the mental functions of individuals. Mental health is not only related to medical or psychological problems, but also has a socio-cultural dimension to the spiritual and religious dimensions. For this reason, not only medical treatment but also religious handling, such as being patient, getting used to implementing and disciplining commendable habits, doing positive activities, increasing confidence in certain values (truth, beauty, virtue, faith and others), reading prayers, read Al-Quran, remembrance of remembrance and hadith of the Prophet, performing evening prayers, associating with people who are good or pious, fasting, follow Islamic studies, follow recitations of recitation and jurisprudence, follow the Assembly of Remembrance and learning Da'wah and science Islam.